Trade openness and economic growth in East African Community economies: A panel causality test - KISAVA, Zakayo S.; MYOVELLA, Godwin A. (Journal of Economics Library, 2018)
Abstract. In spite of financial liberalization that has been discussed and studied over the past decades, the debate for the East African Community (EAC) still remain open on the relationship between trade openness and economic growth that has a link with trade-economic policies. This paper analyzes the relationship by employing the modern methodology of Dumistrescu & Hurlin (2012) Panel Causality test, The Test involved a scope of 46 years from 1970-2016. The empirical finding shows that there is a bidirectional movement (causality) as trade openness increase or relaxed lead to the growth of the economy in the East African Community. The results are supported by the endogenous growth theory that openness increases economic growth. There is a feedback relationship. The main operational implication of these empirical results is that the governments of the East African economies should dismantle barriers to trade to make sure that their intended objective is not ephemeral. Keywords. East African Community, Economic growth, Panel causality test, Trade openness. JEL. C59, F43, O24.